2021
DOI: 10.3389/fdmed.2021.780973
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune Microenvironment in Maxillofacial Bone Homeostasis

Abstract: Maxillofacial bone defects are common medical problems caused by congenital defects, necrosis, trauma, tumor, inflammation, and fractures non-union. Maxillofacial bone defects often need bone graft, which has many difficulties, such as limited autogenous bone supply and donor site morbidity. Bone tissue engineering is a promising strategy to overcome the above-mentioned problems. Osteoimmunology is the inter-discipline that focuses on the relationship between the skeletal and immune systems. The immune microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 127 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…Cytokines are important in regulating bone homeostasis and immune functions ( Horowitz, 1998 ). The differentiation and activation of the bone cells including the osteoclasts and osteoblasts are driven by cytokines and immune cells ( Li et al, 2021 ). Thus, the role of various cytokines on bone metabolism during LPS-induced immune challenge was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are important in regulating bone homeostasis and immune functions ( Horowitz, 1998 ). The differentiation and activation of the bone cells including the osteoclasts and osteoblasts are driven by cytokines and immune cells ( Li et al, 2021 ). Thus, the role of various cytokines on bone metabolism during LPS-induced immune challenge was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the mRNA expression of TNF-α , IL-17, and IFN-γ tended to increase in the tibia of LCA-fed hens challenged with LPS injection. In a recent review, these immune cytokines (TNF-α, IL-17, and IFN-γ) were identified as particularly significant in stimulating bone resorption and suppressing bone formation, which ultimately leads to inflammatory bone loss ( Li et al, 2021 ). Thus, it is evident that low Ca supply during immune challenge would exacerbate the incidence of bone loss and dysregulate bone homeostasis in aged laying hens.…”
Section: Discussionmentioning
confidence: 99%